PENERAPAN APLIKASI UJIAN BERBASIS KOMPUTER UNTUK MENINGKATKAN KUALITAS PENDIDIKAN PADA SMP - Mingsep R. Sampebua; Semuel B. Membala (LPPM Uncen, 2018)
The purpose of the dedicaton activity is to apply computer based test application using PHP programming and MySQL database, train and practice the use of computer based test application to the students junior high school Advent Abepura. Method of implementing activities adopting the pattern of action research which includes program planning, program implementation, evaluation, and report. Implementation of the service activities includes seven stages of coordinating with the junior high school Advent Abepura, creating computer based test application software, socialization about the application of computer based test, training and practice of using computer based test application, mentoring the use of computer based test application, and report generation. The result of the activity is the students are able to use computer based test application so that it can improve the quality of education at junior high school Advent Abepura. This overcomes the student's cheating factor in the exam process, improves teacher's objectivity in the assessment, cost savings in the problem-making / replication process and answer sheets, speeding up the examination and assessment of the exam results. Keywords: Computer based test, PHP web, Application software, Education quality